2017
DOI: 10.1002/2017jd026736
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Summer Extreme Precipitation Events on the Hydrothermal Dynamics of the Active Layer in the Tanggula Permafrost Region on the Qinghai‐Tibetan Plateau

Abstract: The characteristics of long‐term variation for extreme precipitation events were analyzed at the Tanggula site in the continuous permafrost regions of the Qinghai‐Tibetan Plateau (QTP). In addition, the impacts of extreme precipitation events in summer on soil thermal‐moisture dynamics were also investigated. The results showed that local extreme precipitation indices fluctuated significantly and that the trend magnitudes of local very wet days (R95p), annual total wet‐day precipitation (PRCPTOT), number of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 75 publications
(89 reference statements)
0
24
0
Order By: Relevance
“…Theoretically, rainfall can increase soil moisture and enhance thermal conductivity of the soil 23 especially for a field such as site A where the soil is far from saturated. Although recent studies have suggested that there remains uncertainty about the impact of precipitation on the thermal regime of the active layer, 24,25 it is possible that abundant precipitation strengthened the thawing of the active layer in summer based on our observations.…”
Section: Resultsmentioning
confidence: 55%
“…Theoretically, rainfall can increase soil moisture and enhance thermal conductivity of the soil 23 especially for a field such as site A where the soil is far from saturated. Although recent studies have suggested that there remains uncertainty about the impact of precipitation on the thermal regime of the active layer, 24,25 it is possible that abundant precipitation strengthened the thawing of the active layer in summer based on our observations.…”
Section: Resultsmentioning
confidence: 55%
“…The annual mean air temperature and accumulated precipitation recorded at a national weather station (Wudaoliang station) near the Xidatan region is shown in Figure 8A, with results indicating that both the air temperature and the amount of precipitation in the area have noticeably increased over the past 40 years. Recent studies have demonstrated that the occurrence of a wet climate on the QTP can reduce the thermal responses of permafrost to warming, thereby preventing the degradation of permafrost, especially in arid and semiarid zones (Zhang et al, 2021), however, the extreme precipitation events in summer can have a thermal impact on permafrost (Zhu et al, 2017). Meanwhile, persistent climate warming is also the reason for the enhanced permafrost degradation in this region.…”
Section: Possible Reasons For the Abrupt Disappearance Of The Permafrost Islandmentioning
confidence: 99%
“…As a result, soil moisture during this period is higher than in the other months that have abundant precipitation. This is especially true for the extreme precipitation events (Zhu et al, 2017). It is also worth noting that precipitation is a predominant source for soil moisture (Zhu, Wu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%